Sowing seeds of change, joining forces to build resilience in agricultural communities by integrating climate, peace, and security - Kenduiywo, Benson; Chepngetich, Brenda; Villa, Victor; Belli, Anna; Korir, Victor Kipkurui; Karanja, Regina; Kiogora, Joseline (2023)
In a dynamic collaborative effort, The Alliance of Bioversity International and the International Center for Tropical Agriculture through CGIAR Climate Resilience initiative (ClimBeR), partnered with the Ministry of Agriculture and Livestock Development - Climate Change Unit - and the Climate-Smart Agriculture Multistakeholder Platform (CSA MSP) to develop a ground-breaking course titled Climate, Peace, and Security in the Agriculture Sector: Unpacking the Climate Change, Agriculture, and Peace Nexus.